Determining Factors of Contractor Tender Winning in Construction Projects - Rosmariani Arifuddin; Ezra Artahsasta; Muh Rifan Fadlillah; Syarif Burhanuddin (Journal of Engineering and Sustainable Development, 2025)
Many participants experience failure because they cannot handle the associated risks. Some do not even know the risks that can derail their tenders. The purpose of the study was to investigate the influence of construction service providers' bidding strategies.  Data collection was carried out through a literature study of previous research to identify influential factors in winning contractor tenders. A questionnaire survey was then conducted to determine which factors were most influential, and these were analyzed using the SmartPLS application. The study’s result reveal some important insights into the factors affecting tender success in Indonesia, including the high influence of financial factors (87.0% for medium qualifiers and 88.2% for significant qualifiers), the strong influence of technology and information systems factors (72.5% for medium qualifiers and 69.5% for significant qualifiers), the significance of factors between intermediate and large qualifying contractors such as human resources having a more significant influence on intermediate qualifiers (64.8%) than large qualifiers (54.7%), and the high significance of construction safety plan factors (68.1% for intermediate qualifiers and 55.9% for significant qualifiers). An in-depth understanding of these factors and their interactions can help contractors develop more effective tendering strategies and improve Indonesia's construction industry's quality and efficiency.